The Impact of 1960s Social Protests on the American Society - Djedidi, Mecheri,Souhila Fatma Zahra; Oman, Khaoula (University of El-oued, 2021)
American history is full of social movements that either succeeded or failed in affecting the participants' and bystanders' lives and rights. Perhaps one of the most important periods regarding social protests is the sixties, which witnessed the birth of the Civil Rights movement, the Women Liberation Movement, the Anti-Vietnam War movement, the Gay movement, and the Environmental movement. These protests have inspired many minorities to fight for their rights, which impacted the American society on many levels. The aim of this study to investigate the impact of these movements on the American society. We conduct the research in a qualitative fashion based on the descriptive and historical methods to investigate these movements' roots and, more importantly, their outcomes and effects on the studied society. Four impact categories are studied: cultural, political, economic, and social. This study reveals that after the movements, the lives of the concerned people have improved even though the progress has been slow. Nevertheless, there is still a considerable gap between the concerning minorities and the White American man.
Keywords: American society, impact, Social movements, the Sixties, ,.